Detection of rhythmic discharges in newborn EEG signals. - Mohseni, H; Mirghasemi, H; Shamsollahi, M; Zamani, MR (2006)
This paper presents a scalp eletroencephalogram (EEG) rhythmic pattern detection scheme based on neural networks. rhythmic discharges detection is applicable to the majority of seizures seen in newborns, and is listed as detecting 90% of all the seizures. In this approach some features based on various methods are extracted and compared by a modified multilayer neural network in order to find rhythmic discharges. Statistical performance comparison with seizure detection schemes of Gotman et al. and Liu et al. is performed.